Remediation of Heavy Metal Contaminated Soil by Using Chemical Stabilization - Yin, Chun Yang; Md Ghazaly, Shaaban; Hilmi, Mahmud (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/